THE ROLE OF WOMEN'S ENTREPRENEURSHIP IN INCLUSIVE ECONOMIC DEVELOPMENT: A SOCIO-PHILOSOPHICAL APPROACH - Maksumova, Umidakhon Sodiqjonovna (Oriental Journal of History, Politics and Law, 2026)
This article examines the role of women's entrepreneurship in promoting inclusive economic development from a socio-philosophical perspective. The study explores the relationship between gender equality, human capital, economic thinking, and social inclusion. Women's entrepreneurship is interpreted not merely as a form of economic activity but as a social institution that facilitates human development, social justice, and sustainable development. The research employs socio-philosophical analysis, systems approach, comparative analysis, and the axiological method. The findings demonstrate that strengthening women's entrepreneurship contributes not only to economic growth but also to social cohesion, equal opportunities, and inclusive development.